Generalized Semistrongly Convex Fuzzy Sets - Sabir, Pishtiwan O. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The intention of this work is to study various aspects on the concepts of generalized convex fuzzy sets, generalized strongly convex fuzzy sets, and generalized semistrongly convex fuzzy sets. Precisely has investigated the properties and relations among them.
Keywords: Fuzzy sets Fuzzy convex sets,Semistrongly convex fuzzy sets